2001
DOI: 10.1126/science.1058092
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Complex Polyketides in a Metabolically Engineered Strain of E. coli

Abstract: The macrocyclic core of the antibiotic erythromycin, 6-deoxyerythronolide B (6dEB), is a complex natural product synthesized by the soil bacterium Saccharopolyspora erythraea through the action of a multifunctional polyketide synthase (PKS). The engineering potential of modular PKSs is hampered by the limited capabilities for molecular biological manipulation of organisms (principally actinomycetes) in which complex polyketides have thus far been produced. To address this problem, a derivative of Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
625
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(653 citation statements)
references
References 19 publications
9
625
0
6
Order By: Relevance
“…To further confirm the above result by in vitro analysis, the recombinant PKS AzlA(ΔDH 1 ), which bears the same site‐directed mutation in the DH 1 domain as above, was successfully expressed in soluble form in Escherichia coli BAP122 with post‐translational modification of the ACP 1 domain. In a one‐pot reaction with 4‐guanidinobutyric acid, purified Azl4 (ligase), Azl5 (acyltransferase), and AzlA(ΔDH 1 ), the starter unit 4‐guanidinobutyryl‐CoA was produced and loaded onto the ACP L domain that comprises the LM in AzlA(ΔDH 1 ).…”
mentioning
confidence: 81%
“…To further confirm the above result by in vitro analysis, the recombinant PKS AzlA(ΔDH 1 ), which bears the same site‐directed mutation in the DH 1 domain as above, was successfully expressed in soluble form in Escherichia coli BAP122 with post‐translational modification of the ACP 1 domain. In a one‐pot reaction with 4‐guanidinobutyric acid, purified Azl4 (ligase), Azl5 (acyltransferase), and AzlA(ΔDH 1 ), the starter unit 4‐guanidinobutyryl‐CoA was produced and loaded onto the ACP L domain that comprises the LM in AzlA(ΔDH 1 ).…”
mentioning
confidence: 81%
“…Khosla and colleagues 50 reported titres of B25 mg l À 1 in the initial reconstruction of polyketide synthesis in E.coli, while the Keasling group obtained maximum amorphadiene titres of 112 mg l À 1 in the first reported synthesis in an engineered organism 51 . These low titres were observed in spite of the availability of natural pathways to produce the target molecules.…”
Section: Resultsmentioning
confidence: 99%
“…109 Together our groups have used these systems to establish the substrate specificity and stereochemistry of numerous PKS domains, as well as the key protein structural, biochemical, and stereochemical features that determine the highfidelity programming of complex modular polyketides. [110][111][112][113][114][115][116][117][118] For example, we have recently shown that KR domains are responsible for controlling the stereochemistry of not only the reduced hydroxyls but also the adjacent methyl substituents of 2-methyl-3-hydroxyacyl-ACP intermediates and also established that redox inactive KR domains harbor an intrinsic epimerase activity ( Figure 15). [119][120][121][122][123][124] A coherent, well-supported picture has emerged in which the ordered processing of pathway intermediates has been shown to involve a complex balance of specific protein-substrate and protein-protein interactions.…”
Section: Enzymology and Molecular Genetics Of Natural Product Biosyntmentioning
confidence: 99%